Fifth International Conference on Quality Software (QSIC'05)
DOI: 10.1109/qsic.2005.36
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Categories and Choices in Activity Diagrams

Abstract: The choice relation framework (CHOC'LATE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…De la Riva et al (2006) developed a partition-based approach where categories and choices are identified by systematically examining both the XML schema and the XML query. Chen et al (2005) and Hartmann et al (2005) introduced their methods to identify categories and choices from UML activity diagrams, which are just one component in a specification. Thus, our review indicates that a systematic identification technique for the entire informal specification does not exist.…”
Section: Identification Of Categories Choices and Their Relationsmentioning
confidence: 99%
“…De la Riva et al (2006) developed a partition-based approach where categories and choices are identified by systematically examining both the XML schema and the XML query. Chen et al (2005) and Hartmann et al (2005) introduced their methods to identify categories and choices from UML activity diagrams, which are just one component in a specification. Thus, our review indicates that a systematic identification technique for the entire informal specification does not exist.…”
Section: Identification Of Categories Choices and Their Relationsmentioning
confidence: 99%
“…The approach proposed in [12] aims to visualize use cases and therefore automated test generation can be facilitated. Visualizing use cases or their scenarios for the purpose of better understanding and analyzing them is a common practice [2,10] and the idea of activity diagram-based test generation is also promoted in [7,17]. Both the approaches proposed in [13] and [9] can generate analysis models including class and activity diagrams.…”
Section: Related Work and Comparisonmentioning
confidence: 99%
“…For example, dSPACE developed the tool AutomationDesk which uses activity diagrams for test descriptions and test script generation [16,17]. Chen et al [20] presented a framework that can construct test cases from specifications by identifying a set of input categories for the activity diagrams as test cases. However, their method requires preliminary information provided by testing experts.…”
Section: Related Workmentioning
confidence: 99%